An Analysis The Types of Code Mixing Used by The Characters in Indonesian Movie Entitled “Dignitate” - Grace Yudita, Putu Andhina (IKIP Siliwangi, 2025)
Code mixing is a linguistic phenomenon that commonly occurs in multilingual societies, including in the world of film. This research aims to explore the use of code mixing in the context of film as a means of cultural expression and intercultural communication. The research method used is qualitative analysis of various film examples from various genres and countries. This study highlights that code mixing in films can represent the cultural identity of certain characters, locations, or social groups. This is reflected in the simultaneous or alternate use of different languages, including a mixture of local languages with foreign languages or official languages with informal dialects. Code mixing can also be used to enhance humor, express deeper emotions, or show the social status of characters in the story. Code mixing in films is not just a linguistic coincidence but a conscious choice that can enrich narratives, bring characters to life, and connect audiences with the multilingual richness that exists in the real world. This research has the potential to provide guidance for filmmakers in utilizing code mixing effectively to achieve broader communicative and artistic goals.